Shakespeare and the digital world : redefining scholarship and practice - Carson, Christie; Kirwan, Peter (Cambridge : Cambridge University Press, 2014)
Due to the unique cultural capital of his works, Shakespeare has long been the test subject for new methods and digital advances in arts scholarship. Shakespeare sits at the forefront of the digital humanities - in archiving, teaching, performance and editing - impacting on scholars, theatres and professional organisations alike. The pace at which new technologies have developed is unprecedented (and the pressure to keep up is only growing). This book offers seventeen new essays that assess the opportunities and pitfalls presented by the twenty-first century for the ongoing exploration of Shakespeare. Through contributions from a broad range of scholars and practitioners, including case studies from those working in the field, the collection engages with the impact of the digital revolution on Shakespeare studies. By assessing and mediating this sometimes controversial digital technology, the book is relevant to those interested in the digital humanities as well as to Shakespeare scholars and enthusiasts.
Shakespeare in the digital humanities / John Lavagnino -- Getting back to the library, getting back to the body / Bruce R. Smith -- Sensing the past : tablets and early modern scholarship / Farah Karim-Cooper -- Webs of engagement / David McInnis -- Internal and external Shakespeare : constructing the twenty-first-century classroom / Erin Sullivan -- Shakespeare at a distance / Sarah Grandage and Julie Sanders --'All great Neptune's ocean' : iShakespeare and play in a transatlantic context / Sheila T. Cavanagh and Kevin A. Quarmby --'From the table of my memory' : blogging Shakespeare in/out of the classroom / Peter Kirwan -- All's Well that Ends Orwell / Sharon O'Dair -- Unlocking scholarship in Shakespeare studies : gatekeeping, guardianship, and open-access journal publication / Eleanor Collins -- Living with digital incunables, or : a'good-enough' Shakespeare text / Katherine Rowe -- Shakespeare in virtual communities / Peter Holland -- Gamekeeper or poacher? : personal blogging/public sharing / Sylvia Morris -- Changing a culture at the Shakespeare Birthplace Trust : championing freedom and democracy / Paul Edmondson and A.J. Leon -- Developing a digital strategy : engaging audiences at Shakespeare's Globe / Ryan Nelson -- The impact of new forms of public performance / Stephen Purcell -- Creating a critical model for the twenty-first century / Christie Carson -- Digital dreaming / Christie Carson and Peter Kirwan.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Shakespeare, William, -- 1564-1616 -- Study and teaching -- Technological innovations; Shakespeare, William, -- 1564-1616 -- In mass media; Literature and technology